Pubertal growth in height, sitting height and leg length in achondroplasia - T. J. Cole; M. del Pino; P. Adamo; V. Fano (Taylor & Francis Group, 2021)
Background: Children with achondroplasia (ACH) appear to lack a pubertal growth spurt in height. Aim To explore the growth spurt in height and its segments sitting height and leg length, in a large sample of ACH cases using growth curve modelling. Subjects and methods: Height and sitting height were measured longitudinally in ACH children, and the data were analysed using the SITAR (SuperImposition by Translation and Rotation) growth model, which estimates a mean growth curve and random effects for individuals defining differences in size, pubertal timing and intensity. Results: Out of 402 ACH children, 85 boys and 75 girls aged 7-20 years had respectively 529 and 454 measurements of height and sitting height, with leg length calculated by difference. SITAR analysis identified peaks in mean height velocity at 13.3 and 11.3 years in boys and girls, with peak velocities of 4.3 and 4.4 cm/year. Mean peak velocity for sitting height was 3.0 cm/year, but leg length showed no peak. The SITAR models explained 92% to 99% of the cross-sectional variance. Conclusion: ACH children do experience a growth spurt in puberty, but only half that of control children. The spurt is due entirely to sitting height, with no leg length spurt.